A warlike culture? Religion and war in the Aztec world. - Pennock, Caroline Dodds (History & Anthropology, 2023)
The Aztec-Mexica people of Tenochtitlan were, by their own definition, a 'warlike' culture, their collective identity closely tied to military ideals and behaviours. The values of war were dramatized and re-enacted at every level of society, and their shared warrior identity was widely understood by both men and women. This was also a culture in which religion and the supernatural were so deeply embedded in belief and behaviour that it is almost impossible to distinguish religious practice from everyday activities. Attempts to 'rationalize' Mesoamerican approaches to warfare often stem from a laudable desire to demystify Indigenous cultures, to recognize their sophistication, and to refute accusations of superstition and savagery. But any attempt to disentangle religion from practice deprives Aztec structures of the very logic scholars seek to instil. For the Indigenous peoples of Mexico, religion was rational: it provided explanations, motivations, structures and identities. One did not go to war solely for religious reasons, but the process of reasoning, of decision making, occurred within a universe in which the physical and metaphysical were interwoven. For the Aztecs, warfare was a sacred act performed in the service of the gods. They framed themselves as warriors, not only in tangible terms, but historically, mythically and metaphorically. Warfare was inextricable from belief in Tenochtitlan, and only by seeing the Aztecs within their own frame of reference, giving value and meaning to their rituals and histories, can we understand the conjunction of religion and war in their embracing and active vision of the cosmos.